Neuro Fuzzy Based Unified Power Quality Conditioner for Power Quality Improvement Fed Induction Motor Drive - R. Saravanan; P.S. Manoharan (IAES International Journal of Artificial Intelligence (IJ-AI), 2015)
The unified power quality conditioner (UPQC) plays an important role in the constrained delivery of electrical power from source to an isolated pool of load or from a source to the grid.  In this paper presents neuro fuzzy based unified power quality conditioner. The series converter is used to compensate voltage sag/swell compensation. The shunt converter is used to compensate reactive power compensation present in the linear and nonlinear load. The performance of neuro fuzzy and with artificial neural network controller is compared. This approach eliminates the total harmonic distortions efficiently. The performance of proposed system is analysed using Mat lab/Simulink.